(untitled) (Daffodil International University Journal of Science and Technology, 2011)
The present study was conducted to identify and determine the prevalence and intensity of infestation brought about by the endoparasites in Channa punctatus (Bloch,1793) from different water bodies of varying water quality in Bangladesh. The prevalence of endoparasites in the host fish Channa punctatus was 91.30% in female and 88.88% in male fishes, among them in sewage water fishes the prevalence was 85.71% in female and 86.66% in male and in fishes collected from a hatchery the prevalence was 100% in both the male and female fishes. The intensities of infestation in Channa punctatus was 6.78 in female and 6.55 in male fish collected from hatchery; and in sewage water fishes the intensity was 3.50 in females and 1.15 in males respectively. Six parasite species were found from polluted water fishes and seven species of parasites were recorded from fresh water fishes. The intensity and the prevalence were higher in host fishes collected from hatchery than the sewage water host fishes. Keywords: Endoparasitic; Infestation; Channa punctatus; Hatchery; Sewage; Lagoon DOI: http://dx.doi.org/10.3329/diujst.v6i2.9339 DIUJST 2011; 6(2): 6-10